Kefungsian keluarga dan perkaitannya dengan motivasi pencapaian: satu kajian di Kementerian Sumber Manusia - Ahmad Khairuddin Mohd Ghazi,; Haikal Anuar Adnan,; Daniella Mokhtar,; Najwa Afiqa Rohaizad,; Nazuha Shamshuddin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Family functioning and achievement motivation are two aspects that have been frequently discussed by psychologists. Findings from previous research found that both aspects are related to each other. The objective of this research was to identify the levels of family functioning and motivation achievements among civil servants from the Ministry of Human Resources. Besides that, this research intended to observe the influence of family functioning towards motivation achievement of the same sample. This research involved 945 respondents comprised of employees with different grades and position within the Ministry of Human Resource in which they were chosen via simple random sampling. The Family Functioning Style Scale (FFSS) was used to measure family functioning while the Cassidy and Lynn Achievement Scale (CLAM) was used to measure achievement motivation. Analysis was carried out using Statistical Package for Social Science (SPSS) version 22 on the data collected. Results showed that majority of the respondents were found to have high levels of family functioning, however, majority of the respondents reported average level of achievement motivation. Results also found that family functioning was influential to motivation achievement.